Poetic Ponderings of Being at Home/Not at Home: (Em)bodiment in the Spaces In-Between - Hébert, Cristyne (Journal of the Canadian Association for Curriculum Studies, 2016)
This poetic inquiry grapples with the notion of home—what it means to be at home in all of its de/generative possibilities of dis/placement, be/longing, and be/coming. Home, as a place that one is from, is explored by way of the tensions in-between place and self, highlighted through a series of personal vignettes. In working through what it means to inhabit the space in-between, the author calls attention to the limits of language for representing the in-between within a text, detailing the constraints of the dash and ampersand and offering the slash as a possible means of representation.